Chemotherapy Curability in Leukemia, Lymphoma, Germ Cell Tumors and Gestational Malignancies: A Reflection of the Unique Physiology of Their Cells of Origin - Savage, Philip (Frontiers in Genetics, 2020)
Cytotoxic DNA damaging chemotherapy brings clinical benefits in the treatment of many metastatic malignancies. However routine curative treatment remains restricted to a small number of malignancies including acute leukaemia, high grade lymphoma, germ cell tumours, gestational malignancies and some of the rare childhood cancers. The detailed explanation for this dramatic divergence in outcomes remains to be elucidated. However, we have previously argued that there is a strong correlation between presence of the unique genetic events of immunoglobulin gene variable/diversity/joining (VDJ) recombination, somatic hypermutation (SHM), meiosis, nuclear fusion and gastrulation occurring in cells of origin of these malignancies and their high sensitivity to DNA damaging chemotherapy. In this study we have reviewed some of the basic physiological information relating to the specialised activity and sensitivity to DNA damage mediated apoptosis of normal cells undergoing these processes. In each of unique genetic events there are dramatic changes in apoptotic sensitivity. In VDJ recombination and somatic hypermutation over 95% of the cells involved undergo apoptosis, whilst in meiosis and nuclear fusion there are dramatic short term increases in the apoptotic sensitivity to DNA damage. It is apparent that each of the malignancies arising during these processes retains some of the unique phenotype associated with it. The impact of the physiological differences is most clearly seen in the two non-mutational malignancies. Gestational choriocarcinoma which arises shortly after nuclear fusion is routinely curable with chemotherapy whilst CIMP-positive ependymomas which is not linked to any of the unique genetic events is highly resistant. A similar pattern is found in a pair of malignancies driven by a single driver mutation. Infantile acute lymphoblastic leukaemia (ALL) arises in a cell undergoing the early stages of VDJ recombination and has a 40% cure rate in contrast paediatric rhabdoid malignancy which is not linked to a unique genetic event responds very poorly to chemotherapy treatment. The physiological changes occurring in cancer cells at the time of the malignant transformation appear to have a major impact on the subsequent sensitivity to chemotherapy and curability. New therapies that impact on these pathways may be of therapeutic value.